A preliminary theory of change detailing how women's participation can improve the management of local forests and fisheries - Leisher, C.; Booker, F.; Agarwal, B.; Day, M.; Matthews, E.; Prosnitz, D.; Roe, D.; Russell, D.; Samberg, L.; Sunderland, T.C.H.; Temsah, G.; Wilkie, D. (Center for Open Science, 2017)
What are the known factors that improve resource governance and conservation when women have a say in the management of local forests and fisheries? We reviewed a large body of literature to address this question and identified 11 studies that compare the governance and conservation results of mixed-gender resource management groups with men-only or women-only groups. The assembled evidence, while neither wide nor deep, forms the basis for a preliminary theory of change as to how participation of women in resource management groups can result in improved resource governance and conservation. Compared to men-only or women-only resource management groups, mixed-gender groups in the included studies tend to have greater community compliance with resource use rules, more transparency and accountability, better conflict resolution, increased patrolling and enforcement, and greater equity of access to resources. They also tend to have more effective resource conservation. There are, however, a number of inclusionary and exclusionary factors that influence women’s participation in forest or fishery management, and the local context appears to be critical in enabling mixed-gender forest and fisheries management.